2000
DOI: 10.1002/(sici)1098-1136(200003)30:1<1::aid-glia1>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1 selectively up-regulates CCR1 expression in primary murine astrocytes

Abstract: Chemokine receptors dictate the cellular responses to chemokines on target cells. Therefore, the regulation of expression of chemokine receptors is likely a crucial point for the regulation of chemokine action. Here we show that CC chemokine receptor 1 (CCR1) expression by primary mouse astrocytes is increased after transforming growth factor beta1 (TGFbeta1) stimulation. TGFbeta1 caused a pronounced up-regulation of CCR1 mRNA in a concentration- and time-dependent manner. TGFbeta1-mediated increase of CCR1 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…Our previous studies demonstrated that stimulation of primary neonatal mouse astrocytes with 1-10 nM RANTES induced chemokine and cytokine transcription, including de novo induction of mRNA for KC, RANTES, MIP-1α, MIP-2, MCP-1, TNF-α, and IL-6 (6,8). Astrocytes were shown to express two high affinity RANTES receptors, CCR1 (CC chemokine receptor 1) and CCR5 (5,6,24). These seven-transmembrane spanning G protein-coupled receptors are often coupled to G proteins that modulate adenylyl cyclase activity (9).…”
Section: Decreased Intracellular Camp Levels After Rantes Stimulationmentioning
confidence: 99%
“…Our previous studies demonstrated that stimulation of primary neonatal mouse astrocytes with 1-10 nM RANTES induced chemokine and cytokine transcription, including de novo induction of mRNA for KC, RANTES, MIP-1α, MIP-2, MCP-1, TNF-α, and IL-6 (6,8). Astrocytes were shown to express two high affinity RANTES receptors, CCR1 (CC chemokine receptor 1) and CCR5 (5,6,24). These seven-transmembrane spanning G protein-coupled receptors are often coupled to G proteins that modulate adenylyl cyclase activity (9).…”
Section: Decreased Intracellular Camp Levels After Rantes Stimulationmentioning
confidence: 99%
“…Other names for the receptor are CC CKR1, HM145, MIP‐1α/R, 12 CMKBR1, 13 LD78 receptor, 14 and MIP‐1α/RANTES R 9 . Since its isolation, CCR1 expression has been reported on several different cell types, e.g., B cells, T cells, neutrophils, monocytes, eosinophils, platelets, and astrocytes 9,10 , 15–18 . So far, eight chemokines have been identified as CCR1 agonists: macrophage inflammatory protein 1α (MIP‐1α/CCL3), regulated on activation of normal T cell expressed and secreted (RANTES/CCL5), monocyte chemoattractant protein 3 (MCP‐3/CCL7), hemofiltrate CC chemokines 1, 2, and 4 (HCC‐1/CCL14; HCC‐2/CCL15; HCC‐4/CCL16), myeloid progenitor inhibitory factor 1 (MPIF‐1/CCL23) (reviewed in 12 ), and monocyte chemoattractant protein 2 (MCP‐2/CCL8) 19 …”
mentioning
confidence: 99%
“…Microglia have previously been shown to express CCR3 and CCR5, receptors for CCL4 and CCL5 (Albright et al, 1999). Astrocytes also express CCR3, in addition to CCR1, another receptor for CCL5 (Flynn et al, 2003; Han et al, 2000). Additionally, previous cuprizone studies have shown that chemokine mRNA transcripts are upregulated in the brain during cuprizone treatment; including, CCL4 and CCL5 (Biancotti et al, 2008; McMahon et al, 2001).…”
Section: Discussionmentioning
confidence: 99%